Results 1 to 3 of 3

Thread: (x^3)(dy/dx) +(2-3x^2)(y)= x^3

  1. #1
    Super Member
    Joined
    Mar 2014
    From
    malaysia
    Posts
    909
    Thanks
    2

    (x^3)(dy/dx) +(2-3x^2)(y)= x^3

    the correct ans is 2y=(x^3) +c(x^3)(e^-(x^2) ) , but my ans is -2y=(x^3) +c(x^3)(e^-(x^2) ) , which part of my working is wrong ? (x^3)(dy/dx) +(2-3x^2)(y)= x^3-pio.jpg
    Follow Math Help Forum on Facebook and Google+

  2. #2
    MHF Contributor
    Joined
    Dec 2013
    From
    Colombia
    Posts
    1,994
    Thanks
    729

    Re: (x^3)(dy/dx) +(2-3x^2)(y)= x^3

    You dropped a minus sign in your last line.
    Follow Math Help Forum on Facebook and Google+

  3. #3
    Super Member
    Joined
    Mar 2014
    From
    malaysia
    Posts
    909
    Thanks
    2

    Re: (x^3)(dy/dx) +(2-3x^2)(y)= x^3

    Quote Originally Posted by Archie View Post
    You dropped a minus sign in your last line.
    y = -0.5(x^3) +c(x^3)(e^-(x^2) )

    i multiply the whole equation with -2 , i got -2y = (x^3) +c(x^3)(e^-(x^2) ) , which part is wrong ?
    Follow Math Help Forum on Facebook and Google+

Search Tags


/mathhelpforum @mathhelpforum